iNVESTMENT IN SECONDARY SCHOOL EDUCATION: WHICH WAY FORWARD TO REDUCE THE COST OF EDUCATION IN SIAYA COUNTY - Sika, James Ochieng (Advances in Social Sciences Research Journal, 2016)
uNIT COST OF SECONDARY EDUCATION HAS CONTINUED TO RISE BOTH DIRECT AND INDIRECT JEOPADOZING ACCESS TO BASIC EDUCATION. THE DEABATE HAS CONCENTRATED ON WHO SHOULD CARRY THE BURDEN OF SECONDARY EDUCATION. HOWEVER DEBATE ON STRATEGIES HAS NEVER BEEN IN THE FOCUS. THIS STUDY BRINGS TO THE FORE SOME SPECIFIC STRATEGIES THAT CAN REDUCE THE COST OF EDUCATION. THE DESCRPTIVE AND CAUSAL COMPARATIVE DESIGNS WERE USED IN THIS STUDY. THE SAMPLE COMPRISED 85 HEADTEACHERS, 765 TEACHERS 3349 STUDENTS AND ONE DEO. THE FINDINGS OF THE STUDY INDICATE THAT ON AVARAGE 86 PERCENT HOUSEHOLDS ARE LOW INCOME EARNERS AND THEREFORE UNABLE TO PAY FEES AND SECONDARY SCHOOLS ARE OWED MILLIONS OF SHILLINGS BY FEE DEFAULTERS. AMONG THE STRTEGIES PROPOSED INCLUDE REDUCING CHARGES ON NON - DISCETIONARY ITEMS AND BUILDING DAY SCHOOLS.